2017
DOI: 10.1530/ec-17-0158
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 15 structural abnormalities: effect on IGF1R gene expression and function

Abstract: Insulin-like growth factor 1 receptor (IGF1R), mapping on the 15q26.3 chromosome, is required for normal embryonic and postnatal growth. The aim of the present study was to evaluate the IGF1R gene expression and function in three unrelated patients with chromosome 15 structural abnormalities. We report two male patients with the smallest 15q26.3 chromosome duplication described so far, and a female patient with ring chromosome 15 syndrome. Patient one, with a 568 kb pure duplication, had overgrowth, developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 69 publications
5
29
0
Order By: Relevance
“…In addition, qRT-PCR and western blotting confirmed the interrelationship between miR-23a and GAS5 at the transcriptional and protein levels. A previous study has shown that the lncRNA GAS5 can negatively regulate expression of miR-23a and that it can act as a miR-23a sponge [46] , which was in line with our conclusion. Furthermore, there is evidence that GAS5 expression is decreased in gastric cancer tissues and is negatively related to increased miR-23a expression [35] .…”
Section: Discussionsupporting
confidence: 93%
“…In addition, qRT-PCR and western blotting confirmed the interrelationship between miR-23a and GAS5 at the transcriptional and protein levels. A previous study has shown that the lncRNA GAS5 can negatively regulate expression of miR-23a and that it can act as a miR-23a sponge [46] , which was in line with our conclusion. Furthermore, there is evidence that GAS5 expression is decreased in gastric cancer tissues and is negatively related to increased miR-23a expression [35] .…”
Section: Discussionsupporting
confidence: 93%
“…There were no differences in either the IGF-1R mRNA or protein levels. Both increased and decreased expression of the gene coding for IGF-1R (IGF1R) may play a role in the etiology of neurological disorders, as previous studies have described [Cannarella et al, 2017;Witsch et al, 2013]. We are the first to report on the levels of IGF-1R in human idiopathic autism.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, cryptorchidism and genital abnormalities have often been observed in patients with 15q structural abnormalities involving the IGF1R locus (Cannarella et al ., ). Such findings indicate a possible role of the IGF1/IGF1R signaling in testicular development, descent, and volume, and in genital differentiation.…”
Section: Evidence In Humansmentioning
confidence: 97%
“…After reviewing the literature, we found that cryptorchidism and other gonadal abnormalities often occur both in patients with 15q chromosome duplications and in those with ring chromosome 15 syndrome. Hence, we hypothesized that IGF1R , which maps on the 26.3 15q chromosomal band, may play a role in the onset of such features (Cannarella et al ., ). To further evaluate this topic, we focused our attention on the effects that the insulin‐like growth factor (IGF) system (mainly IGF1, IGF2, IGF1 receptor [IGF1R], insulin receptor substrates [IRS]) plays on testicular development and function.…”
Section: Introductionmentioning
confidence: 97%